Comparison of preoperative locoregional Ga‐68 PSMA‐11 PET‐CT and mp‐MRI results with postoperative histopathology of prostate cancer. Issue 9 (23rd April 2019) - Yilmaz, Burcak; Turkay, Rustu; Colakoglu, Yunus; Baytekin, Halil F.; Ergul, Nurhan; Sahin, Selcuk; Tugcu, Volkan; Inci, Ercan; Tasci, Ali I.; Cermik, Tevfik F.
Abstract: Background: Conventional imaging modalities are inadequate to evaluate locoregional extension of prostate cancer (PCa). The aim of the current retrospective study was to investigate the diagnostic efficacy of Gallium‐68 prostate‐specific membrane antigen‐11 (Ga‐68 PSMA‐11) positron emission tomography/computed tomography (PET/CT) and multiparametric magnetic resonance imaging (mp‐MRI) for staging preoperative PCa patients with correlating histopathology. Materials and Methods: Twenty‐four patients with histologically proven PCa underwent both Ga‐68 PSMA‐11 PET/CT and mp‐MRI before robot‐assisted laparoscopic radical prostatectomy. For each tumor area, correlations with histopathological results were defined for tumor localization, extraprostatic extension (EPE) of the tumor, invasion of seminal vesicle (SVI) and bladder neck invasion (BNI). In patients with regional lymph node (LN) dissection, histopathological results were also correlated with imaging modalities. Results: Sensitivity, specificity, positive predictive value, negative predictive value, and accuracy for detection of EPE and SVI were higher for mp‐MRI than Ga‐68 PSMA‐11 PET/CT. On the other hand Ga‐68 PSMA‐11 PET/CT had significant successful results for detection of LN metastases when compared with mp‐MRI. But for BNI detection both modalities had same insufficient results. Ga‐68 PSMA‐11 PET/CT had strong results for appropriate tumor localization in the gland. Conclusion: Ga‐68 PSMA PET/CT has superior results for assessing local LN metastases and for intraprostatic tumor localization. Whereas, mp‐MRI must be the preferred modality for determining SVI and EPE. But both imaging modalities failed for determining BNI accurately. Both modalities should be used in conjunction with each other for better treatment planning.